Community-acquired pneumonia complicated by rhabdomyolysis: A clinical analysis of 11 cases - Zhao, Bo (World J Clin Cases, 2019)
BACKGROUND: In clinical practice, community-acquired pneumonia (CAP) can be complicated by rhabdomyolysis (RM), and RM symptoms are mild and easily missed during diagnosis. Moreover, available data on RM induced by CAP are mainly from case reports. Due to the relatively low incidence of CAP-induced RM, more systematic studies are required to understand the characteristics of CAP-induced RM to improve its diagnosis and treatment. AIM: To investigate the clinical characteristics of patients with CAP-induced RM. METHODS: This was a retrospective study of 11 patients with CAP-induced RM. Baseline characteristics, diagnostic work-up, and laboratory test results were summarized and compared with those of 48 patients with exercise-induced RM admitted during the same period. RESULTS: CAP-induced RM was more common in men, and affected older patients compared to those with exercise-induced RM. However, the average age of the patients in this study was lower than the age of peak incidence of CAP in adults in China. The major clinical manifestations were high fever and respiratory symptoms. RM symptoms were mild and often overlooked. Patients with CAP-induced RM had elevated inflammatory parameters, respiratory alkalosis, relatively low serum potassium levels and often had abnormalities in hepatic and renal function and cardiac enzymes. Compared with the exercise group, the pneumonia group had lower levels of creatine kinase and myoglobin, a higher incidence of acute kidney injury, and worse renal function and prognosis. Adverse events were mainly related to the severity of CAP. CONCLUSION: CAP-induced RM has different clinical characteristics from those of exercise-induced RM. Early detection and treatment could reduce complications and consequently shorten the treatment course.